2019
DOI: 10.3390/catal9020115
|View full text |Cite
|
Sign up to set email alerts
|

Bleached Wood Supports for Floatable, Recyclable, and Efficient Three Dimensional Photocatalyst

Abstract: To suppress the agglomeration of a photocatalyst, facilitate its recovery, and avoid photolysis of dyes, various support materials such as ceramic, carbon, and polymer have been investigated. However, these support materials pose the following additional challenges: ceramic supports will settle down at the bottom of their container due to their high density, while the carbon support will absorb the UV-vis light for its black color. Herein, we propose a floatable, UV transmitting, mesoporous bleached wood with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Compared to DW, the prepared DW/CNT composite was floatable with a 20% higher steam generation capacity and had better solar energy utilization due to an increased thermal efficiency of 8%. In another study, [17] He et al prepared a floatable 3D DW infiltrated with a titanium dioxide (TiO 2 )-based photocatalyst for methylene blue photocatalytic degradation. The Figure 19.…”
Section: Membrane Distillation and Solar Stream Generation Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to DW, the prepared DW/CNT composite was floatable with a 20% higher steam generation capacity and had better solar energy utilization due to an increased thermal efficiency of 8%. In another study, [17] He et al prepared a floatable 3D DW infiltrated with a titanium dioxide (TiO 2 )-based photocatalyst for methylene blue photocatalytic degradation. The Figure 19.…”
Section: Membrane Distillation and Solar Stream Generation Membranesmentioning
confidence: 99%
“…DW is chemically hydrophilic due to the presence and exposure of hydroxyl groups and possible sites for DW functionalization. DW scaffolds have been functionalized for various applications such as transparent wood, [ 13,14 ] high performance thermal insulators, [ 15 ] energy generation systems, [ 16 ] nanostructured wood membranes, [ 17,18 ] carbonized wood nanocomposites, [ 19 ] and other bioinspired woods. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…These composites remove pollutants through the combined action of adsorption and photodegradation. Several TiO 2 wood and wood-based composites [6,18,19] removed VOCs while [14,15,[20][21][22] removed organic dyes. Adding to this list are the metal-doped TiO 2 wood and wood-based composites [13,23,24] which removed VOCs while [25,26] removed organic dyes.…”
Section: Tio 2 -Treated and Metal-doped Tio 2 -Treated Wood And Wood-based Compositesmentioning
confidence: 99%
“…It can be clearly identified that the solution after evaporation exhibits yellow color due to the leaching of natural wood. However, it is clean and pollution-free for DL-wood, and benign to the environment (He et al 2019).…”
Section: Lignin Content and Propertiesmentioning
confidence: 99%